Evaluation of Spatial-Temporal Variations of Incoming Solar Radiation in Kermanshah Province Using "Liu and Jordan" Model - Firouz Mojarrad; Amanollah Fathnia; Saeed Rajaee Najafabadi (تحقیقات کاربردی علوم جغرافیایی)
The aim of this study was to provide a reliable estimate of the amount of solar radiation in Kermanshah province by using “Liu and Jordan” model in order to develop solar sites. The amount of atmospheric elimination in each month was calculated using an index called clearness index () and the results were applied on different slopes, aspects and heights. Then, according to the obtained results, amounts of direct, diffuse and total radiation were calculated in different slopes of the region and the relevant maps were consequently drawn. The results showed that the minimum amount of atmospheric elimination and thus the maximum amount of received radiation in the province occurs in late spring and summer due to the increase of clearness index () with a maximum of 1360 cal/cm2/day in May. the least amount of received radiation occurs in Janury equal to 386.3 cal/cm2/day. Radiation variations at the provincial level are high between lowlands and highlands in Janury and December, according to the angle of radiation and significant elevation changes in the region. However, in summer, distribution of surface radiation is almost identical because of high solar radiation, and thus standard deviation amount of received radiation is reduced. The highest amount of radiation is received in Javanrood city as much as 528.1 cal/ cm2/day due to greater heights, and the lowest amount is received in Qasr-e Shirin city as much as 443.6 cal/ cm2/day due to lower heights.